PENGARUH QUALITY OF WORK LIFE (QWL) DAN MOTIVASI TERHADAP KINERJA PEGAWAI KECAMATAN DI KABUPATEN KULONPROGO D.I YOGYAKARTA - Susilo Ari Wibowo (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2017)
The purpose of this research is to look at the effect Quality of Work Life,  Need for Achievement,  Need  for Affiliation, dan  Need  for Power, on the performance of the employees subdistrict of Kulon Progo regency Special Province of Yogyakarta.The data collection was conducted by distributing questionnaires addressed to the 267 employees,  to obtain an answer for each item of respondents' perception of the research variable statement. Of the tota questionnaires distributed, 214 questionnaires were returned and readily processed. The data analysis method used was multiple regression analysis to examine the effect Quality of Work Life,  Need for Achievement,  Need  for Affiliation, dan  Need  for Power, on the performance.The test conducted partially showed that Quality of Work Life,  Need for Achievement,  Need  for Affiliation  have a significant positive impact on the performance of  the employees subdistrict of Kulon Progo regency. On the other hand, Need  for Power  does not affect the performance of the employees  subdistrict of Kulon Progo regency. While the test conducted simultaneously showed that Quality of Work Life,  Need for Achievement,  Need  for Affiliation, dan  Need  for Power  have a significant positive impact on the performance of the employees subdistrict of Kulon Progo regency.